Litchi in winter season – a way forward - Nath, Vishal; Kumar, Amrendra; Pandey, S D; Tripathi, P C (Indian Horticulture, 2015)
Presently, very little area has been brought under litchi in theseregions. The area has may advances for litchi which hasencouraged many farmers to go for large plantation under litchi.The NRC, Litchi, is providing all possible technology back-upto growers in the region. A systematic technology demonstration in the region can further boost the litchi production to increase the Indian fruit basket with litchi, particularly in off-season.